The Role of Coastal Women In Processing Waste Plastic to Support The Household Economy and Sustainability of Fishery Resources In Galesong Subdistrict, Takalar District - Mardiyah, Nisfah Ainun; Amiluddin, Amiluddin; Arief, Andi Adri; Amri, Andi; Wahid, Abdul (PONGGAWA : Journal of Fisheries Socio-Economic, 2021)
The presence of women as one of the development potentials is felt to be very urgent because now the Indonesian nation is currently at a very important momentum in realizing development. The purpose of this study is to determine the perceptions and behavior in managing plastic waste for the sustainability of fisheries resources, and the dynamics of management and the role of coastal women in plastic waste processing and to find out how big the contribution of the role of coastal women in processing plastic waste to support the household economy. The research was conducted in August 2020 in Galesong District, Takalar Regency. Determination of respondents using a census technique, by determining all the number of informants based on the involvement of coastal women's groups in processing waste with considerations and goals that are considered to be able to provide data to a maximum of 30 people. The data analysis uses Household Income Analysis and Contribution and Likert Scale, which analyzes the data interactively and uses questionnaires. From the research results, it was found that there are perceptions and behaviors of coastal women in processing plastic waste and the dynamics of plastic waste management so that coastal women have a contribution to household income and the sustainability of fisheries resources.